Kościół powszechny i Kościoły lokalne w nauczaniu papieża Franciszka - Nawracała, Tomasz (Poznańskie Studia Teologiczne, 2018)
Mutual relations between the universal Church and local Churches belong to topics whose meaning increases and which return systematically in theological discussions. Hence also the short pontifi- cate of Pope Francis is not deprived of certain elements that allow a different view of the issue of the liaison between the two ecclesial communities. The article presents Francis’ view on the relation- ship between the universal Church and local Churches, showing the dependence of papal views on the theological thinking of Cardinal Walter Kasper. At the same time, two additional issues (Peter’s primacy and the formulation of the particular Church) are indicated, which are important for the papal ecclesiology.